On absolutely continuous change of measure and Markov property of stochastic processes - Grigelionis, B. (Lithuanian Mathematical Journal, 1969)
The abstracts (in two languages) can be found in the pdf file of the article.Original author name(s) and title in Russian and Lithuanian:Б. Григелионис. Об абсолютно непрерывной замене меры и марковском свойстве случайных процессовB. Grigelionis. Apie absoliučiai tolydinį mato pakeitimą ir atsitiktinių procesų Markovo savybę